Dyadic perspectives on advice between friends: Relational influence, advice quality, and conversation satisfaction. Issue 4 (2nd October 2017) - Guntzviller, Lisa M.; MacGeorge, Erina L.; Brinker, David L.
ABSTRACT: Theory on advice currently gives insufficient attention to relational context, the interaction, and the advisor's perspective. We conceptualize advice interactions as dyadic processes within relationships, and examine how relationship assessments influence perceptions of advice and the interaction. Friends reported on their relationships (152 dyads, N  = 304), had conversations that included advice, and then rated advice quality and conversational satisfaction. An actor–partner interdependence model supported a "mutual influence model:" both advisors and recipients were influenced by their own and their partners' assessments. For advisors and recipients, higher ratings of partners' past support increased their own advice quality ratings and conversation satisfaction, and higher advice quality increased conversation satisfaction. Relationship reports from the partner's perspective impacted individuals' outcomes in unexpected ways.